Pengembangan Game Blooket untuk Meningkatkan Minat Belajar Siswa pada Materi Fiqih Muamalah Sebagai Media Pembelajaran di MTS Hidayatul Muhajirin Palangka Raya - Maulida Sari; Jasiah Jasiah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to develop and design the Blooket Game, Blooket is a website-based interactive learning platform in the form of a quiz game that functions as a learning media in class and can increase student learning interest in Fiqh Muamalah material as a learning media at Mts Hidayatul Muhajirin Palangka Raya. The method used is development research (R&D) with the Borg and Gall model, which includes ten stages but the researchers here only take four stages, namely: 1) Identification of Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation and researchers added one more stage, namely 5) Main Trial. So in this study there are five stages developed. The research subjects consisted of 30 students of class IX MTs Hidayatul Muhajirin. Data was collected through Google Forms given to students after the use of the media, as well as feedback on students' learning experiences in the classroom. The results showed that the use of Blooket educational game significantly increased students' interest in learning. With the average score of students' interest in learning before the use of the media was 50%, and increased to 90% after implementation in the classroom. In addition, students also showed higher enthusiasm in following the learning and actively participating in learning activities. This study concludes that Blooket educational game-based learning media can be an alt.